2005
DOI: 10.2307/20777571
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of NSF Support for Basic Research In Economics

Abstract: We are grateful to the NSF for providing access to the data. Data collection and analysis were partially supported by a grant from the Heinz School. We are indebted to Ruth Williams of the NSF for help in getting access to the data, and for patiently answering our questions and queries. Dan Newlon and Lynn Pollnow of the NSF, educated us about the intricacies of the NSF grant procedures in economics, and we thank them for their help and support. We thank Paul David for long and stimulating conversations, and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 0 publications
8
82
0
Order By: Relevance
“…Other studies that examine the funding-output link at the level of the individual researcher tend to find small positive effects (Arora and Gambardella, 2005;Averch, 1987Averch, , 1989. However, these studies recognize the potential for selection bias, which would lead them to overstate the true impact of grant receipt.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that examine the funding-output link at the level of the individual researcher tend to find small positive effects (Arora and Gambardella, 2005;Averch, 1987Averch, , 1989. However, these studies recognize the potential for selection bias, which would lead them to overstate the true impact of grant receipt.…”
Section: Prior Literaturementioning
confidence: 99%
“…However, these studies recognize the potential for selection bias, which would lead them to overstate the true impact of grant receipt. For example, Arora and Gambardella (2005) find that past productivity and other observable researcher characteristics such as institution quality are correlated with NSF award selection even after controlling for reviewer score, suggesting that their estimates may be biased upward. 2 A few earlier studies have examined the effect of research funding provided by NIH in particular.…”
Section: Prior Literaturementioning
confidence: 99%
“…An examination of the literature reveals that the factors influencing faculties' research productivity have been studied for decades. There are a number of factors such as scholarship (Arora and Gambardella, 1996), age and life cycle (Levin and Stephan, 2011), research activity performance of department (Smeby and Try, 2005), scientific collaboration (Lee and Bozeman, 2005), quality of training or individual abilities and skills (Wichian et al, 2009), and faculty motivation and incentives (Monroe and Kumar, 2011b). These factors are generally of two types: individual variables and environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, ample empirical evidence suggesting that STI policy should be concerned with the provision of adequate funding of public science. Research grants are found to increase individual productivity (Stephan, 1996;Lee and Bozeman, 2005) although this relationship is moderated by the scientist's career stage (Arora and Gambardella, 2006) and the size of the grant (Godin, 2003). Moreover, most research grants are intended to stimulate collaborative behaviour among scientists (Defazio et al, 2009).…”
Section: Policy Context and Rationalementioning
confidence: 99%